2021
DOI: 10.1177/00207640211042917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smartphone addiction and its correlates in a sample of Egyptian university students

Abstract: Background: Smartphone addiction is considered currently as a public health concern especially among university students. Aim: The study assesses the prevalence of smartphone addiction and its sociodemographic and psychiatric correlates among Egyptian university students. Methods: A random sample of 1,380 undergraduate Egyptian university students from different universities were assessed using the smartphone addiction short scale, Beck depression Inventory, Beck anxiety Inventory, Pittsburgh sleep Quality Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 66 publications
(82 reference statements)
2
17
0
Order By: Relevance
“…Firstly, our study found that possible SAD and depressive symptoms were statistically significant risk factors for PSU, which is consistent with most previous studies ( Enez Darcin et al, 2016 ; Elhai et al, 2017 , 2019 ; Okasha et al, 2021 ). According to the model of compensatory internet use proposed by Kardefelt-Winther (2014) , electronic devices such as smartphones can be viewed as an avoidance-coping strategy, which provides a feasible substitution of discomforting face-to-face contact with the social situations for individuals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Firstly, our study found that possible SAD and depressive symptoms were statistically significant risk factors for PSU, which is consistent with most previous studies ( Enez Darcin et al, 2016 ; Elhai et al, 2017 , 2019 ; Okasha et al, 2021 ). According to the model of compensatory internet use proposed by Kardefelt-Winther (2014) , electronic devices such as smartphones can be viewed as an avoidance-coping strategy, which provides a feasible substitution of discomforting face-to-face contact with the social situations for individuals.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of PSU observed in our sample was higher than that of young people in other countries such as Switzerland (16.9%) ( Haug et al, 2015 ), Japan (26.4%) ( Tateno et al, 2019 ), United Kingdom (38.9%) ( Sohn et al, 2021 ), Spain (12.5%), and Belgium (21.5%) ( Lopez-Fernandez, 2017 ) using the SAS-SV. However, similar to our study, Okasha et al (2021) investigated 1,380 Egyptian university students and found that the prevalence rate of PSU was 59.6%. This discrepancy across studies may be due to the economic differences between different countries.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, other studies found male students were at high risk of smartphone addiction [ 33 , 83 ]. Meanwhile, some studies did not find any gender difference in smartphone addiction [ 1 , 84 , 85 ]. These inconsistent findings warrant further studies whether gender is a significant factor in smartphone addiction.…”
Section: Discussionmentioning
confidence: 99%
“…There were several de nitions of smartphone problematic use. According to some authors, it is the inability to limit phone use, which eventually disrupts users' functioning (19,26,29,32,40,47,48). While, other authors claimed that smartphone problematic use was a type of behavioral addiction that included salience, preoccupation, tolerance, withdrawal, and compulsive symptoms (30,33,34,38,41,44,48).…”
Section: Psu De Nitionmentioning
confidence: 99%